Group Business Plan - In-Sight - Mehta, Monil; Hamlai, Aditi; Farzad, Photographer (2010)
Executive Summary This Business plan is the initiative of a group of three enthusiastic MBA students with a passion for business development, aspiring to bring a fresh approach to the advertising industry. ‘In-Sight Inc.’ is the result of this dream. In-Sight is being formed with the objective of providing firms with creative advertising solutions through a range of products that will serve as an innovative marketing medium, which proposes to help these firms increase their brand awareness and visibility. The Business Idea The U.K. advertising industry has witnessed several changes over the years. The mediums through which companies advertise have evolved over the years and companies are now moving away from conventional forms of advertising and towards innovative mediums to spread their message. The spends on advertising have also declined over the years as has the size of the advertising industry. To capitalize on these opportunities presented to us, we at In-Sight will provide non conventional innovative advertising solutions to firms. Initially we will target companies based in East Midlands. We will endeavour to provide our partnered clients with low cost, high impact marketing solutions that will reach their target market. We plan to provide companies with an opportunity to market their brand and create visibility by displaying their logos on products that are consumed on a daily basis by their target group. This will involve identifying two sets of companies. Firstly, those companies that would be ready to consume items of daily use, (paper cups, paper napkins, pens etc.) being supplied free of cost with another company’s logo printed on them. These would be small and medium sized firms that we would categorise as ‘receiving companies’. Secondly, firms looking to increase their visibility and brand awareness. Articles of daily use bearing such companies logos could be distributed amongst the former companies free of cost. These would be medium and large sized firms that we would categorise as ‘sponsoring companies’. Thus unlike other media firms that are selling advertising, In-Sight is providing a common platform for ‘sponsoring’ and ‘receiving’ companies to fulfil their needs. We have identified this as a gap in the market and see this as an opportunity to establish a successful business. Marketing Activities As a new venture we will aim to create brand awareness and increase visibility. Thus we will undertake several promotional activities throughout the first year, such as promotion through social networking sites, our own website, sending samples to prospective partnering firms, distributing brochures and word-of-mouth publicity among others. We will endeavour to constantly build a loyal client base and increase the number of firms we partner with. Operations In-Sight will be based out of Nottingham and will be set up in line with the legal requirements of the United Kingdom. We plan to outsource the production of the products we offer along with printing on the same to a supplier based in India. The products have been designed in the form of packages to suit the varying needs of clients. Financing the Business The initial start-up capital required to fund In-Sight shall be contributed by the three founders in equal proportions. By the end of the first year, we believe we can nearly reach a break-even point through the revenue generation model adopted. Our projected financial analysis suggests that revenues should increase three fold by the end of the year 2013 by constantly seeking to expand our customer base, we should be in a position to achieve a target of half a million. We will constantly look to expand our customer base. We plan to achieve a target of half a million GBP by 2015 having an average 21% EBIT (earnings before interest and taxes) and finally having EAT (earning after tax) of 13% over a period of five years. After having grown In-Sight into a well established profitable business, we may look to spread operations beyond the region of East Midlands. To make such plans successful, we may seek financial assistance from venture capitalists or angel investors. Creating Social Awareness In-Sight realizes the importance of social awareness and will look to promote several social causes. We will offer our partnering companies an opportunity to be socially responsible through the recycling services we provide to them. Thus we believe this concept has a promising future and has the potential to create a niche for itself in the advertising industry.